2020
DOI: 10.3390/d12060221
|View full text |Cite
|
Sign up to set email alerts
|

Rusty Blackbird Habitat Selection and Survivorship during Nesting and Post-Fledging

Abstract: Rusty blackbird (Euphagus carolinus) populations have declined dramatically since the 1970s and the cause of decline is still unclear. As is the case for many passerines, most research on rusty blackbirds occurs during the nesting period. Nest success is relatively high in most of the rusty blackbird’s range, but survival during the post-fledging period, when fledgling songbirds are particularly vulnerable, has not been studied. We assessed fledgling and adult survivorship and nest success in northern New Hamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The presence of dense patches of conifers in the vicinity of those wetlands was also required for nesting, while stand age and harvest history were less influential [24]. Lack of specificity in the latter matches the largely anecdotal descriptors of nest substrates reported elsewhere; rusty blackbirds appear to prefer nesting in short (less than 4.5m tall), dense conifer stands [21,22,[25][26][27], and predominantly use black spruce (Picea mariana) and balsam fir (Abies balsamea) near wetlands [24]. They have also been reported nesting in willow thickets (Salix sp.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…The presence of dense patches of conifers in the vicinity of those wetlands was also required for nesting, while stand age and harvest history were less influential [24]. Lack of specificity in the latter matches the largely anecdotal descriptors of nest substrates reported elsewhere; rusty blackbirds appear to prefer nesting in short (less than 4.5m tall), dense conifer stands [21,22,[25][26][27], and predominantly use black spruce (Picea mariana) and balsam fir (Abies balsamea) near wetlands [24]. They have also been reported nesting in willow thickets (Salix sp.…”
Section: Introductionmentioning
confidence: 97%
“…; [23]). Most recently, Wohner et al [27] assessed rusty blackbird habitat use during various periods of the breeding season. They found that streams, softwood and mixed wood sapling stands, wetlands, and areas characterized by slopes between 1% and 8% were important in predicting rusty blackbird occupancy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations